The Association of Transfer Rate From Hospitals Without Revascularization Capabilities and Mortality Risk for Older Non–ST‐Segment Elevation Myocardial Infarction Patients - Shen, Lan (Clin Cardiol, 2015)
BACKGROUND: Interhospital transfer invasive management patterns and implications for older non–ST‐segment elevation myocardial infarction (NSTEMI) patients initially presenting to non–revascularization‐capable hospitals have not been explored. HYPOTHESIS: Patients admitted to hospitals with a higher transfer proportion have lower risk of long‐term mortality. METHODS: We linked CRUSADE Registry data on 5678 patients age ≥65 years from 65 United States non–revascularization‐capable hospitals (2003–2006) with inpatient Medicare longitudinal claims. Hospitals were categorized according to hospital‐level patient transfer‐out rates, low (≤40%) vs high (>40%). The associations between transfer‐out rates and 30‐day, 6‐month, and 3‐year mortality risk were evaluated using Cox proportional hazard models. RESULTS: Hospital‐level transfer‐out rates varied widely (median, 43%; interquartile range, 31%–54%). Compared with patients from low–transfer‐out hospitals (n = 2715), patients from high–transfer‐out hospitals (n = 2963) were more likely to be male, less likely to have renal insufficiency and prior heart failure, and had lower long‐term CRUSADE mortality risk scores. These patients also more commonly received evidence‐based acute medications before transfer and underwent subsequent revascularization after transfer. The adjusted risks of mortality at various time intervals were similar for those from high– vs low–transfer‐out hospitals: 30 days (hazard ratio: 0.95, 95% confidence interval: 0.79‐1.14), 6 months (0.97, 0.84‐1.12), and 3 years (1.01, 0.91‐1.11). CONCLUSIONS: Transfer rates for older NSTEMI patients vary widely among non–revascularization‐capable hospitals. Despite lower predicted mortality risk and higher rates of post‐transfer revascularization, patients from high–transfer‐out hospitals had a similar risk for short‐ and long‐term mortality compared with those from low–transfer‐out hospitals.